2014
DOI: 10.1017/s0950268814001137
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between socioeconomic indices and potentially zoonotic pathogens carried by wild Norway rats: a survey in Rhône, France (2010–2012)

Abstract: SUMMARYLeptospira interrogans, hantaviruses (particularly Seoul virus), hepatitis E virus (HEV), and Toxoplasma gondii are rat-associated zoonoses that are responsible for human morbidity and mortality worldwide. This study aimed to describe the infection patterns of these four pathogens in wild rats (Rattus norvegicus) across socioeconomic levels in neighbourhoods in Lyon, France. The infection or exposure status was determined using polymerase chain reaction or serology for 178 wild rats captured in 23 locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 39 publications
6
47
1
1
Order By: Relevance
“…The frequency of rats seropositive for T. gondii was consistent with previous studies, which reported a prevalence of 0.3% to 8% in other rodent species 15,16 . No signifi cant differences between sexes were found in the frequency of T. gondii seropositive rats (p = 0.730) or sampling locations (p = 0.614) ( Table 3).…”
supporting
confidence: 91%
“…The frequency of rats seropositive for T. gondii was consistent with previous studies, which reported a prevalence of 0.3% to 8% in other rodent species 15,16 . No signifi cant differences between sexes were found in the frequency of T. gondii seropositive rats (p = 0.730) or sampling locations (p = 0.614) ( Table 3).…”
supporting
confidence: 91%
“…To determine influences of demographic and habitat characteristics on the prevalence of Leptospira and rat PyV as well as their respective coinfections, generalised linear modelling (GLM) with a binomial error distribution was applied. Individual infection status was treated as the response variable, with sex and body weight, which is often used to distinguish between age classes [here defined as ≤200 g (juvenile/subadult) and >200 g (adult)], as demographic predictors and habitat (urban, town, rural) based on human population density, which has often been associated with disease prevalence in rats …”
Section: Methodsmentioning
confidence: 99%
“…Individual infection status was treated as the response variable, with sex and body weight, which is often used to distinguish between age classes [here defined as ≤200 g (juvenile/subadult) and >200 g (adult)], 54 as demographic predictors and habitat (urban, town, rural) based on human population density, which has often been associated with disease prevalence in rats. 53,54 Here, we used data generated by the Geostat project which provides high-resolution (1 km 2 ) human population data based on the European census of 2011 (Eurostat, 2012). 55 To categorise human density, the approach by Giné et al 56 was applied.…”
Section: Statisticsmentioning
confidence: 99%
“…Research has suggested that human exposure to rats is common in areas with high population density, such as inner-city economically-challenged neighborhoods (Davis 1953, Childs et al 1998, Langton et al 2001, Battersby et al 2002, Reis et al 2008, Walsh 2014, Ayral et al 2015. The effects of rodent management (with or without rodenticide) on the reduction of zoonoses are not well understood.…”
Section: Impacts To California and Californiansmentioning
confidence: 99%